Partha Chatterjee Omnibus (New Delhi, 1997)
The Omnibus is comprised of three of Partha Chatterjee's finest works, marking a significant phase in the author's intellectual journey as a political scientist. The principal object of study in all three books is the existing nation state. i.e. Nationalist thought and the colonial world; The nation and its fragments and A possible India.
Keywords: Nationalism